Growth development and dry matter yield of 16 Lucerne genotypes cultivated in south Tunisia - Hayek T.; Loumerem M.; Nagaz K.; Thabet M. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
This study aims to compare the growth and forage dry matter yield of 16 different Lucerne (Medicago sativa) genotypes, under the specific environmental conditions of south Tunisia. Plants were cultivated on the field and irrigated during the period (March 2005 to September 2007) and a water deficit treatment was applied, by interrupting irrigation, for 43, 56 and 65 days during the summer of 2005, 2006 and 2007, respectively. Results show significant differences between genotypes regarding forage dry matter yield, leaf-to-stem ratio and drought sensitivity index. Some genotypes show an interesting yield potential, mainly Ecotipo Siciliano, and to a lesser extent, ABT 805 and Ameristand 801S. Therefore, those varieties can provide local farmers in the region with a possibility for an alternative use.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)